Environmentally friendly anti-halation glass and preparation method thereof
By using oxides such as SnO2 and Bi2O3 in anti-halo glass, environmentally friendly anti-halo glass is prepared, which solves the harmful problems of heavy metal ions to the environment in the prior art, and achieves efficient elimination of stray light and high temperature stability. Meets the needs of a variety of application scenarios.
Patent Information
- Application Number
- CN202310258999.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-17
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2043-03-17
AI Technical Summary
The heavy metal ions such as As2O3, Sb2O3, PbO used in existing anti-halo glasses are harmful to the environment, affecting their visible light transmittance and use effect, and cannot meet the requirements of environmental protection and high temperature stability.
Using SnO2 and Bi2O3 as main components, environmentally friendly anti-halo glass is prepared through specific oxide ratios and heat treatment processes to ensure that the blackened layer thickness is greater than 0.55mm, the visible light transmittance is less than 0.5%, and within the range of 30-380℃. It has a suitable coefficient of thermal expansion and a high strain point temperature.
It realizes green and environmentally friendly anti-halo glass, with high mechanical strength and high temperature stability, can effectively eliminate stray light and meet the requirements of optical instruments for cathode sensitivity, and is suitable for a variety of application scenarios.
Smart Images

Figure BDA0004130504340000021 
Figure BDA0004130504340000031 
Figure BDA0004130504340000041
Abstract
Description
Technical Field
[0001] The present invention relates to the field of special glass materials, in particular to an environmentally friendly anti-halation glass material and a preparation method thereof, belonging to the technical field of glass materials. Background Art
[0002] Anti-halo glass is different from ordinary glass. It is covered with a layer of black glass with a certain thickness, namely the blackening layer. This blackening layer of glass has the characteristics of low transmittance in the visible light range and can withstand high temperatures of about 500°C. The blackening layer is hard, wear-resistant, scratch-resistant, and acid- and alkali-resistant.
[0003] The blackened layer of anti-halation glass is produced through a high-temperature reduction heat treatment. When the glass contains ions or valence-modifying ions that can generate color centers or be reduced, and is then heated to approximately 500°C and exposed to reducing gases such as hydrogen, a blackened layer forms on its surface. This layer can generally withstand temperatures around 500°C without affecting its shape or performance. The blackened layer has a low visible light transmittance and absorbs light incident on and reflected from its surface. Therefore, anti-halation glass can eliminate stray light, prevent halation, or filter light. It can effectively eliminate stray light caused by streaks, bubbles, or other defects on and within optical lenses, as well as emitted light from the optical path of optical lenses, thereby improving image resolution and image recognition sensitivity, and enhancing the optical performance of various optical instruments and equipment. It is often used as an anti-halation and anti-glare filter in detectors and optical lenses. It can also be used in the input windows of various detectors, cameras, camcorders, and optical lenses of various optical instruments and equipment, and is a key material in various high-definition lenses.
[0004] Generally speaking, as long as ions that can generate color centers or can be reduced are added to the glass, the glass surface can be reduced and colored. If all stray light is to be absorbed and the required performance is to be achieved, the concentration of ions that can generate color centers or can be reduced in the glass cannot be too low, and the thickness of the black glass layer cannot be too thin. Currently, the anti-halation glass on the market mainly relies on the surface blackening of the glass layer produced by hydrogen treatment with As2O3, Sb2O3, PbO and other ions added to the glass. However, the existing anti-halation glass on the market still has various problems in terms of the thickness and size of the blackening layer, the transmittance of the blackening layer, and environmental protection requirements. In particular, environmentally harmful heavy metal ions such as As2O3, Sb2O3, and PbO have a "poisoning" effect on the cathode sensitivity of optical lenses and other optical instruments, seriously affecting the visible light transmittance and performance requirements of the anti-halation glass, causing the anti-halation and anti-glare effects of the anti-halation glass to be greatly reduced.
[0005] Moreover, anti-halation glass is widely used in astronomical observation, engineering monitoring, atmospheric observation, exploration and survey, national defense and military, industrial applications and other aspects. With the gradual strengthening of national strength, the gradual improvement of people's living standards, and the increasingly stringent requirements for environmental protection, the development of an anti-halation glass that can effectively eliminate stray light and is environmentally friendly has important market prospects. Summary of the Invention
[0006] In order to overcome the problems existing in the prior art, the purpose of the present invention is to provide an environmentally friendly anti-halation glass. The present invention also provides a method for preparing the environmentally friendly anti-halation glass.
[0007] To solve the above technical problems, the present invention adopts the following technical solution: an environmentally friendly anti-halation glass, characterized in that it is prepared from the following oxides in accordance with mass percentage (wt.%):
[0008]
[0009] Preferably, it is prepared from the following oxides in weight percentage (wt.%):
[0010]
[0011] The environmentally friendly anti-halation glass of the present invention is characterized in that the total amount of SnO2 and Bi2O3 is 0.5-1.5wt.%;
[0012] The environmentally friendly anti-halation glass of the present invention does not contain any of the metal oxides harmful to the environment, such as As2O3, Sb2O5, BaO, PbO, Tl2O, CdO, BeO, V2O5, etc.
[0013] Furthermore, the environmentally friendly anti-halation glass is characterized in that the average linear thermal expansion coefficient of the glass in the range of 30-380°C is (55±5)×10 -7 / ℃; the strain point temperature of glass is greater than 550℃;
[0014] Furthermore, the environmentally friendly anti-halation glass is characterized in that: after the anti-halation glass is blackened, the thickness of the blackened layer is greater than 0.55 mm, and the visible light transmittance is less than 0.5%;
[0015] The method for preparing an environmentally friendly anti-halation glass according to the present invention is characterized by comprising the following steps:
[0016] (1) Weigh the corresponding raw materials according to the glass composition, mix them evenly, and then put them into a quartz crucible for melting and forming;
[0017] (2) The molten glass is poured into a rod or cast into a round rod shape, and then placed in an annealing furnace for annealing;
[0018] (3) The annealed and cooled glass rod is rounded, sliced, polished, processed, cleaned, dried, and then placed in a reduction furnace for reduction treatment to obtain anti-halation glass with a uniform black layer.
[0019] Compared with the prior art, the environmentally friendly anti-halation glass provided by the present invention has the following significant advantages:
[0020] (1) The present invention does not contain any metal oxides or heavy metal oxides harmful to the environment, such as As2O3, Sb2O5, BaO, PbO, Tl2O, CdO, BeO, V2O5, etc., and is green and environmentally friendly;
[0021] (2) The anti-halation glass of the present invention is blackened from the base, and the blackened layer of the glass has no reflective interface with the base glass. The blackened layer has high mechanical strength and is not easy to fall off or discolor. After the blackening treatment, the thickness of the blackened layer is greater than 0.55 mm, the visible light absorption efficiency is high, and the visible light transmittance is less than 0.5%;
[0022] (3) The strain point temperature of glass is relatively high, which is greater than 550°C and can withstand high temperature thermal shock;
[0023] (4) The thermal expansion coefficient of the present invention is suitable. The average linear thermal expansion coefficient of the glass in the range of 30-380°C is (55±5)×10 -7 / ℃;
[0024] (5) The environmentally friendly anti-halation glass provided by the present invention has both good stray light elimination effect and high cathode sensitivity, which can meet the requirements of cameras and other optical instruments for the cathode sensitivity of the anti-halation input window. DETAILED DESCRIPTION
[0025] In order to make the objectives, technical solutions and advantages of the present invention more clear, the embodiments of the present invention are described in further detail below.
[0026] The present invention will be further described in detail below with reference to specific embodiments, but this is not intended to limit the present invention.
[0027] The present invention provides a method for preparing an environmentally friendly anti-halation glass, which is prepared from the following oxides according to mass percentage (wt.%):
[0028]
[0029]
[0030] Preferably, it is prepared from the following oxides in weight percentage (wt.%):
[0031]
[0032] In the present invention, SiO2 forms the main component of the glass skeleton structure and plays a major role in the glass framework. The mass percentage (wt.%) of SiO2 is 55-70%. A SiO2 content below 55 wt.% makes it difficult to obtain a high strain point glass and also reduces the chemical resistance and mechanical strength of the glass. When the SiO2 content exceeds 70 wt.%, the high-temperature viscosity of the glass increases, resulting in excessively high glass melting temperatures.
[0033] Al2O3 is an intermediate oxide of glass. 3+ There are two coordination states: located in tetrahedra or octahedra. When there is sufficient oxygen in the glass, aluminum oxide tetrahedra [AlO4] are formed, forming a continuous network with silicon oxide tetrahedra. When there is insufficient oxygen in the glass, aluminum oxide octahedra [AlO6] are formed, which are external to the network and located in the cavities of the silicon oxide structure. Therefore, within a certain content range, it can form the main body of the glass network with SiO2 and B2O3. The mass percentage (wt.%) of Al2O3 is 4-18. Al2O3 content below 4wt.% will reduce the chemical and thermal stability of the glass. Al2O3 content above 18wt.% will significantly increase the melting temperature of the glass and increase the glass's crystallization tendency.
[0034] B2O3 is a glass-forming oxide and a component of the glass skeleton. It is also a solvent that reduces the viscosity of the glass during melting. Boron oxide triangles [BO3] and boron oxide tetrahedrons [BO4] are structural components. Boron may exist as triangles [BO3] or boron oxide tetrahedrons [BO4] under different conditions. Under high-temperature melting conditions, it is generally difficult to form boron oxide tetrahedrons and can only exist as trihedrons. However, at low temperatures, under certain conditions, B 3+ It tends to capture free oxygen to form tetrahedra, compacting the structure and increasing the low-temperature viscosity of the glass. However, its characteristic of decreasing glass viscosity at high temperatures and increasing it at low temperatures also dictates a limited range for its content. The mass percentage (wt.%) of B2O3 ranges from 8 to 18. Below 8 wt.%, B2O3 fails to enhance solubility and reduces the chemical stability of the glass. Above 18 wt.%, B2O3 reduces the glass's expansion coefficient and mechanical strength, while increasing its tendency to phase separate.
[0035] Na2O is an external oxide in the glass structure network. The mass percentage (wt.%) of Na2O is 0.4-1.5. When the content of Na2O is lower than 0.4%, the melting viscosity of the glass will increase; when the content of Na2O is higher than 1.5%, the expansion coefficient of the glass will increase.
[0036] K2O is an external oxide in the glass structure network. The mass percentage (wt.%) of K2O is 0.5-9. When the K2O content is lower than 0.5%, the melt viscosity of the glass will increase; when the K2O content is higher than 9%, the expansion coefficient of the glass will increase.
[0037] CaO is an oxide outside the glass structure network. The mass percentage (wt.%) of CaO is 0.2-4. If the CaO content is greater than 4wt.%, the chemical stability of the glass will be reduced and the crystallization tendency of the glass will be increased.
[0038] SrO is a network exogenous oxide in the glass structure. The mass percentage (wt.%) of SrO is 0.5-2. Introducing a network exogenous oxide with similar properties into the glass can further improve the performance of the glass. If the SrO content is greater than 2wt.%, it will reduce the chemical stability of the glass and increase the tendency of the glass to crystallize.
[0039] ZnO is an intermediate oxide in glass, but it typically exists as [ZnO6] octahedrons outside the glass network. When sufficient free oxygen is present in the glass, it can also integrate into the glass network as [ZnO4] tetrahedrons. The weight percentage (wt.%) of ZnO is 0.5-5. A ZnO content below 0.5 wt.% reduces the chemical stability of the glass; a ZnO content above 5 wt.% increases the glass's thermal expansion coefficient and increases its tendency to phase separation.
[0040] TiO2 mainly acts as a stabilizer, which can improve the mechanical strength and chemical stability of glass. The mass percentage (wt.%) of TiO2 is 0.1-0.5. If the TiO2 content is lower than 0.1wt.%, it will not have a stabilizing effect. If the TiO2 content is higher than 0.5wt.%, it will increase the crystallization tendency of the glass.
[0041] Ga2O3 can reduce the thermal expansion coefficient of glass and effectively inhibit glass crystallization. The mass percentage (wt.%) of Ga2O3 is 0-0.1. A Ga2O3 content greater than 0.1wt.% will increase the tendency of glass crystallization.
[0042] SnO2 is primarily used as a glass clarifier to clear bubbles in molten glass. It also acts as a variable ion to enhance the blackening effect of the glass. The mass percentage (wt.%) of SnO2 is 0.05-0.5%. A SnO2 content greater than 0.5wt.% will increase the glass's tendency to crystallize.
[0043] Bi2O3 is the main component of glass blackening, which has the functions of lowering the softening point of glass, making the glass have appropriate fluidity when melting, and adjusting the thermal expansion coefficient of glass. 3+ It mainly exists in the glass network in the form of [BiO6] and [BiO3], with the mass percentage (wt.%) of Bi2O3 being 0.01-1. When the Bi2O3 content is lower than 0.01wt.%, it is difficult to obtain anti-halation glass with a uniform blackening layer, and the chemical resistance of the glass will be reduced. When the Bi2O3 content is higher than 1wt.%, the thermal expansion coefficient of the glass will increase, and the transmittance of the glass will be reduced.
[0044] The environmentally friendly anti-halation glass of the present invention is characterized in that the total amount of SnO2 and Bi2O3 is 0.5-1.5wt.%;
[0045] The environmentally friendly anti-halation glass of the present invention does not contain any of the metal oxides harmful to the environment, such as As2O3, Sb2O5, BaO, PbO, Tl2O, CdO, BeO, V2O5, etc. Even if it contains very small amounts, they are introduced by other glass raw materials.
[0046] Furthermore, the environmentally friendly anti-halation glass is characterized in that the average linear thermal expansion coefficient of the glass in the range of 30-380°C is (55±5)×10 -7 / ℃; the strain point temperature of glass is greater than 550℃;
[0047] Furthermore, the environmentally friendly anti-halation glass is characterized in that: after the anti-halation glass is blackened, the thickness of the blackened layer is greater than 0.55 mm, and the visible light transmittance is less than 0.5%;
[0048] The method for preparing an environmentally friendly anti-halation glass according to the present invention is characterized by comprising the following steps:
[0049] (1) Weigh the corresponding raw materials according to the glass composition, mix them evenly, and then put them into a quartz crucible for melting and forming;
[0050] (2) The molten glass is poured into a rod or cast into a round rod shape, and then placed in an annealing furnace for annealing;
[0051] (3) The annealed and cooled glass rod is rounded, sliced, polished, processed, cleaned, dried, and then placed in a reduction furnace for reduction treatment to obtain anti-halation glass with a uniform black layer.
[0052] The parameters, measuring methods and instruments for the environmentally friendly anti-halation glass of the present invention are as follows:
[0053] (1) Average thermal expansion coefficient α at 30-380℃ 30 / 380 [10 -7 / ℃];
[0054] (2) Strain point temperature of glass T st (℃);
[0055] The linear expansion coefficient of the glass at 30-380°C is measured using a horizontal dilatometer and expressed as the average linear expansion coefficient using the method specified in ISO 7991; the strain point temperature of the glass is T st Determined by testing the glass thermal expansion curve.
[0056] Table 1 Chemical composition (wt.%) and glass properties of the examples
[0057]
[0058]
[0059] The following are the raw materials used in the examples and their requirements:
[0060] Quartz sand (high purity, 150 μm sieve material less than 1%, 45 μm sieve material less than 30%, Fe2O3 content less than 0.01 wt.%), alumina (analytical grade, average particle size 50 μm), boric anhydride (400 μm sieve material less than 10%, 63 μm sieve material less than 10%), sodium carbonate (analytical grade), potassium carbonate (analytical grade), calcium carbonate (analytical grade), strontium carbonate (analytical grade), zinc oxide (analytical grade), titanium oxide (analytical grade), gallium oxide (analytical grade), tin oxide (analytical grade, average particle size 60 μm sieve material less than 1%), and bismuth oxide (analytical grade).
[0061] Example 1
[0062] First, the raw materials were selected according to the glass composition of Example 1 in Table 1, and the Fe content in the glass raw materials was strictly controlled so that the ingredients met the glass chemical composition of Table 1. Then, a quartz crucible was used to melt the glass batch materials at 1550°C for 6 hours. After the glass batch materials were melted into a homogeneous glass melt, the glass melt was poured into a preheated heat-resistant steel mold for casting and then annealed. Its test properties are shown in Table 1. (1) The average linear expansion coefficient at 30-380°C was 52×10 -7 / ℃; (2) The strain point temperature of glass is 553℃.
[0063] Example 2
[0064] The raw materials were selected according to the glass composition of Example 2 in Table 1, and the Fe content in the raw glass materials was strictly controlled so that the ingredients met the glass chemical composition of Table 1. Then, a quartz crucible was used to melt the glass batch materials at 1450°C for 8 hours. After the glass batch materials were melted into a homogeneous glass melt, the glass melt was poured into a preheated heat-resistant steel mold for casting and then annealed. The test properties are shown in Table 1. (1) The average linear expansion coefficient at 30-380°C was 51×10 -7 / ℃; (2) The strain point temperature of glass is 560℃.
[0065] Example 3
[0066] The raw materials were selected according to the glass composition of Example 3 in Table 1, and the Fe content in the glass raw materials was strictly controlled so that the ingredients met the glass chemical composition of Table 1. Then, a quartz crucible was used to melt the glass batch materials at 1500°C for 6 hours. After the glass batch materials were melted into a homogeneous glass melt, the glass melt was poured into a preheated heat-resistant steel mold for casting and then annealed. The test properties are shown in Table 1. (1) The average linear expansion coefficient at 30-380°C was 55×10 -7 / ℃; (2) The strain point temperature of glass is 554℃.
[0067] Example 4
[0068] The raw materials were selected according to the glass composition of Example 4 in Table 1, and the Fe content in the glass raw materials was strictly controlled so that the ingredients met the glass chemical composition of Table 1. The same melting process and test conditions as in Example 1 were used. The basic properties of the samples are shown in Table 1. (1) The average linear expansion coefficient at 30-380°C was 60×10 -7 / ℃; (2) The strain point temperature of glass is 565℃.
[0069] Example 5
[0070] The raw materials were selected according to the glass composition of Example 5 in Table 1, and the Fe content in the glass raw materials was strictly controlled so that the ingredients met the glass chemical composition of Table 1. The same melting process and test conditions as in Example 1 were used. The basic properties of the samples are shown in Table 1. (1) The average linear expansion coefficient at 30-380°C was 53×10 -7 / ℃; (2) The strain point temperature of glass is 575℃.
[0071] The data obtained from the examples show that the environmentally friendly anti-halation glass of the present invention does not contain any environmentally harmful metal oxides or heavy metal oxides such as As2O3, Sb2O5, BaO, PbO, Tl2O, CdO, BeO, V2O5, etc., and is green and environmentally friendly. In addition, the blackening is generated from the substrate, and the blackened layer of the glass has no reflective interface with the substrate glass. The blackened layer has high mechanical strength and is not easy to fall off or discolor. After the blackening treatment, the thickness of the blackened layer is greater than 0.55 mm, and the visible light absorption efficiency is high, with a visible light transmittance of less than 0.5%. The strain point temperature of the glass is relatively high, greater than 550°C, and the glass can withstand high-temperature thermal shock. The thermal expansion coefficient is suitable, with an average linear thermal expansion coefficient of (55±5)×10 -7 / ℃, and is widely used in astronomical observation, engineering monitoring, atmospheric observation, exploration and survey, national defense and military, industrial applications and other aspects.
[0072] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the scope of the present invention. The scope of protection of the present invention is defined by the claims. Those skilled in the art may make any modifications, equivalent substitutions, or improvements to the present invention within the spirit and scope of protection of the present invention, and such modifications or equivalent substitutions are deemed to fall within the scope of protection of the present invention.
Claims
1. An environmentally friendly anti-halation glass, characterized in that: Prepared from the following oxides according to mass percentage (wt.%):
2. The environmentally friendly anti-halation glass according to claim 1, characterized in that: The total amount of SnO2 and Bi2O3 is 0.8-1.4 wt.%.
3. The environmentally friendly anti-halation glass according to claim 1, characterized in that: It contains substantially no environmentally harmful metal oxides such as As2O3, Sb2O5, BaO, PbO, Tl2O, CdO, BeO and V2O5.
4. The environmentally friendly anti-halation glass according to claim 1, characterized in that: The average linear thermal expansion coefficient of the anti-halation glass at 30-380°C is (55±5)×10 -7 / ℃; the strain point temperature of glass is greater than 550℃.
5. The environmentally friendly anti-halation glass according to claim 1, characterized in that: After the anti-halation glass is blackened, the thickness of the blackened layer is greater than 0.55 mm, and the visible light transmittance is less than 0.5%.
6. The method for preparing an environmentally friendly anti-halation glass according to claim 1, characterized in that: The following steps are involved: (1) weighing the corresponding raw materials according to the glass components, mixing them evenly and then placing them in a quartz crucible for melting and forming; (2) draining or casting the melted glass liquid into a round rod shape, and then placing it in an annealing furnace for annealing; (3) The annealed and cooled glass rod is rounded, sliced, polished, processed, cleaned, dried, and then placed in a reduction furnace for reduction treatment to obtain anti-halation glass with a uniform black layer.
